Developing Mn-doped lead sulfide quantum dots for MRI labels - Turyanska, Lyudmila; Moro, Fabrizio; Patanè, Amalia; Barr, James; Köckenberger, Walter; Taylor, Alexander; Faas, Henryk; Fowler, Maxine J.; Wigmore, Peter; Trueman, Rebecca C.; Williams, Huw Edward Llewelyn; Thomas, Neil R. (Royal Society of Chemistry, 2016)
Magnetic interactions of Mn2+ions in lead sulfide (PbS) nanocrystals with protons in water are probed by NMR and MRI. A thin layer of capping molecules enables free solvent diffusion to the nanocrystal surface resulting in a decrease of proton relaxation times. Magnetic resonance imaging of neuronal cell pellets exposed to (PbMn)S at non-toxic concentrations demonstrates their prospects as MRI-labels.